2011
DOI: 10.1007/s00125-011-2342-y
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and diabetes: a two-way relationship

Abstract: Periodontitis is a common chronic inflammatory disease characterised by destruction of the supporting structures of the teeth (the periodontal ligament and alveolar bone). It is highly prevalent (severe periodontitis affects 10–15% of adults) and has multiple negative impacts on quality of life. Epidemiological data confirm that diabetes is a major risk factor for periodontitis; susceptibility to periodontitis is increased by approximately threefold in people with diabetes. There is a clear relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
1,175
7
61

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,325 publications
(1,261 citation statements)
references
References 90 publications
18
1,175
7
61
Order By: Relevance
“…Studies have supported a two-way relation between diabetes and periodontal status [6][7][8][9] . Key public strategies such as primary prevention and early diagnosis require deep knowledge related to risk factors and to the etiopathogenesis of the disease or diseases under analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have supported a two-way relation between diabetes and periodontal status [6][7][8][9] . Key public strategies such as primary prevention and early diagnosis require deep knowledge related to risk factors and to the etiopathogenesis of the disease or diseases under analysis.…”
Section: Discussionmentioning
confidence: 96%
“…The association between periodontal diseases and diabetes has been studied over the last decades and, today, there is enough scientific evidence to support the existence of a twoway relationship between them [6][7][8][9] . Diabetes increases the risk of incidence and severity for periodontitis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Evidence indicates a "two-way" relationship between T2DM and CP. 6,7,8,9 A large number of epidemiological studies have demonstrated that T2DM may increase the risk of CP by two-to three-fold. 10,11,12 Conversely, CP may be a risk factor for worsened glycemic control in diabetic individuals and may increase the risk of related complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by destruction of connective tissue, the periodontal ligament, and alveolar bone, leading to a significant increase of systemic exposure to bacteria (Okada et al, 1996). Many investigators have suggested a two‐way relationship between diabetes and periodontitis (Nagasawa et al, 2010; Nishimura et al, 2003; Preshaw et al, 2012). Interestingly, it has been reported that periodontal infection shows a positive correlation with endothelial dysfunction (Tonetti et al, 2007) and that infection with Porphyromonas gingivalis increases endothelial injury in obese mice (Ao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%